Radial artery mycotic aneurysm due to infective endocarditis: A case report and review of literature. Issue 3 (2018) - Tranmer, Andrew I; Kalmar, Christopher L; Applebaum, Matthew A; DiEgidio, Paul; Capito, Anthony E
No abstract available